2015
DOI: 10.1021/cm504350q
|View full text |Cite
|
Sign up to set email alerts
|

Novel Tb-MOF Embedded with Viologen Species for Multi-Photofunctionality: Photochromism, Photomodulated Fluorescence, and Luminescent pH Sensing

Abstract: The tunable inorganic nodes and modifiable organic linkers enable the designable functionality to come true in the new-type porous hybrid materials, namely metal-organic frameworks (MOFs). By using viologen-functionalized mbenzenedicarboxylate as organic linker, a terbium-organic framework embedded with asymmetric viologen species has been constructed. The reversible photochromism from bright yellow to dark green is implemented due to favorable spatial stack of the electron donor and acceptor. The photochromic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
155
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(169 citation statements)
references
References 64 publications
9
155
0
Order By: Relevance
“…The UV–vis absorption band of p ‐ASA has none overlap band with the emission characteristic band of BUC‐69 at 580, 591, 616, 651, and 700 nm (Figure b), demonstrating that there was none Förster resonance energy transfer (FRET) existing in the quenching emission process. No obvious red shift or blue shift were found the UV–vis absorption peak of BUC‐69 when contact with p ‐ASA in the suspension (Figure a), implying that there is no PET or DEE interactions in the system . All these findings further confirmed that the sensing mechanism could be assigned to the radiative energy transfer process.…”
Section: Resultssupporting
confidence: 57%
“…The UV–vis absorption band of p ‐ASA has none overlap band with the emission characteristic band of BUC‐69 at 580, 591, 616, 651, and 700 nm (Figure b), demonstrating that there was none Förster resonance energy transfer (FRET) existing in the quenching emission process. No obvious red shift or blue shift were found the UV–vis absorption peak of BUC‐69 when contact with p ‐ASA in the suspension (Figure a), implying that there is no PET or DEE interactions in the system . All these findings further confirmed that the sensing mechanism could be assigned to the radiative energy transfer process.…”
Section: Resultssupporting
confidence: 57%
“…As a new class of fluorescence materials, lanthanide metal‐organic frameworks (LnMOFs) have gathered considerable attention for chemical recognition due to the combination of intrinsic luminescence features and inherent porosity of MOFs. In addition to some crystal materials, chemical sensors based on LnMOFs have been widely investigated to detect metal cations, anions, small molecules, gases, temperatures, pH values, and moisture . The wide sensing applications make luminescence MOFs an important member in the club of “smart materials”.…”
Section: Introductionmentioning
confidence: 99%
“…A CP‐based pH sensor molecule should have the functional group that can accept H + or OH – without damaging the framework . Up to now, only few examples of CPs‐based pH fluorescent sensors have been reported, most of which exhibit linear relationships between emission intensities and pH values in certain pH ranges. Some of these pH fluorescent sensors suffer the drawbacks of unconspicuous signal variation and poor reproducibility.…”
Section: Introductionmentioning
confidence: 99%